Verificação da pressão venosa central em unidade de terapia intensiva - Silva, Lidia Maria Beloni (2014)
Introduction: The bedside monitoring in the intensive care unit is considered mandatory safety technology and an indispensable tool in the management of critical patients. The recommended procedures for basic hemodynamic monitoring are: cardiac and respiratory rate, diuresis, continuous electrocardiography, oxygen saturation, noninvasive and invasive mean arterial pressure, temperature, and central venous pressure. Objective: Describe the evidence regarding the procedure of central venous pressure monitoring in the intensive care unit and identify whether there are differences in the values of the pressure with the different angles of the patient’s bedside. Method: We conducted an integrative review of the literature on the scientific databases PubMed, LILACS and SciELO, seeking idenfy scientific literature on the topic. After review, 15 articles were selected. In the second stage we conducted a prospective open study with a quantitative approach, with verification of central venous pressure in four different angles. Data are expressed as absolute numbers and percentages. Variables were analyzed with the Mann-Whitney test and the Wilcoxon test. Associations between measures were test by Pearson’s correlation coefficient (r) Results: Through the reading and discussion of the articles we identified that the monitoring can be performed with the catheter positioned in the superior vena cava and inferior device with single or multilumen, through two systems in the water column or the electronic pressure transducers. Four points should be followed in the monitoring process: mounting system, leveling, zeroing and dynamic response. The values for parameter of normal pressure must consider the point used as the phlebostatic axis and the unit of measurement used. The results should be analyzed together with other monitoring parameters and the patient’s condition. In the second stage 156 patients, checked the central venous pressure in four different angles, totaling 624 measures were included. Conclusion: Further studies are needed to identify whether there are differences between the various forms of performing the procedure, and if the values change according to the technique used. We found a positive linear correlation between the measures 0º and 30º, but in 0 ° and 45 ° the correlation is weak showing little association between the variables.